CRISPR/Cas9-mediated editing of double loci of BnFAD2 increased the seed oleic acid content of rapeseed (Brassica napus L.) - Liu, Han; Lin, Baogang; Ren, Yun; Hao, Pengfei; Huang, Lan; Xue, Bowen; Jiang, Lixi; Zhu, Yang; Hua, Shuijin (Frontiers in Plant Science, 2022)
Seed oleic acid is an important quality trait sought in rapeseed breeding programs. Many methods exist to increase seed oleic acid content, such as CRISPR/Cas9-mediated genome editing system, yet there is no report on seed oleic acid content improvement via this system’s precise editing of the double loci of BnFAD2. Here, precise CRISPR/Cas9-mediated genome editing of the encoded double loci (A5 and C5) of BnFAD2 was established. The results demonstrated high efficiency of regeneration and transformation, with the rapeseed genotype screened in ratios of 20.18% and 85.46%, respectively. The total editing efficiency was 64.35%, while the single locus- and double loci-edited ratio was 21.58% and 78.42%, respectively. The relative proportion of oleic acid with other fatty acid in seed oil of mutants was significantly higher for those that underwent the editing on A5 copy than that on C5 copy, but it was still less than 80%. For double loci-edited mutants, their relative proportion of oleic acid was more than 85% in the T1 and T4 generations. Comparison of the sequences between the double loci-edited mutants and reference showed that no transgenic border sequences were detected from the transformed vector. Analysis of BnFAD2 sequence on A5 and C5 at the mutated locus of double loci mutants uncovered evidence for base deletion and insertion, and combination. Further, no editing issue of FAD2 on the copy of A1 was detected on the three targeted editing regions. Seed yield, yield component, oil content, and relative proportion of oleic acid between one selected double loci-edited mutant and wild type were also compared. These results showed that although the number of siliques per plant of the wild type was significantly higher than those of the mutant, the difference of seed yield and oil content were not significant between them, albeit with the mutant having a markedly higher relative proportion of oleic acid. Altogether, our results confirmed that the established CRISPR/Cas9-mediated genome editing of double loci (A5 and C5) of the BnFAD2 can precisely edit the targeted genes, thereby enhancing the seed oleic acid content to a far greater extent than can a single locus-editing system.